Prostate-Specific Antigen (PSA) Bounces Following Stereotactic Body Radiotherapy for Prostate Cancer: Importance of PSA Test Frequency - Kang, Ki Mun; Choi, Hun Sik; Jang, Hong Seok; Song, Jin-ho (Urology Journal, 2024)
Purpose: Prostate-specific antigen (PSA) bounce is a common phenomenon that can be observed in patients of prostate cancer treated by radiotherapy. However, the clinical, pathological, or dosimetric predictors and clinical significance of PSA bounce in stereotactic body radiotherapy (SBRT) patients is still unknown. Methods: Between August 2006 to December 2015, 74 prostate cancer patients were treated by SBRT with Cyberknife at two medical centers. The prescription dose was 35-37.5 Gy in 5 fractions. Follow-up PSA tests were more frequently performed in one hospital than the other (median 4 vs. 10 times for initial one year). PSA bounce was defined as a rise of 0.2 ng/mL followed by a decline to or below the previous nadir. Results: A total of 74 patients, PSA bounce was observed in 41 patients (55.4%). On univariate analysis, the treated medical center (p = 0.02), PSA follow-up frequency (p = 0.01), patient age (p < 0.01), and total prescription dose (p = 0.03) were significant clinical factors in predicting the incidence of PSA bounce, while in multivariable analysis only the PSA follow-up frequency, and patient age remains significant. Conclusion: PSA bounce was seen in a significant proportion of patients after Cyberknife SBRT. The PSA follow- up test frequency, and patient age were significant factors that were correlated with the incidence of PSA bounces in this study.